(untitled) (Revista de Investigaciones Universidad del Quindío, 2010)
The environmental characteristics of the soils in the Andean agro ecosystems make them susceptible to erosion caused by the intensity and duration of the rains. These effects are intensified by reducing vegetation cover in the stage of soil preparation for cultivation. For these reasons we worked on crops implanted and also it was determined the amount of soil displaced by surface runoff in simulated rainfall at 100 mm h-1 of intensity, yielding a statistical average of eroded soil on the ground for cultivation of 2.6 g and pasture land with 0.2 g. This information allowed the development of an environmental assessment, using the matrix of FEARO (Federal Office for review and environmental analysis), with which it was identified soil, flora and fauna as the most affected environmental components, causing a change in the characteristics of this ecosystem.